The healing function of the word in Iván Rodríguez Chávez’s El angelario de la vida (The Angelarium of Life) - Pantigoso Pecero, Manuel (2023)
This article analyses the curative function of the poems in Iván Rodríguez Chávez’s El angelario de la vida (2023). Thus, it highlights aspects of his poetics, such as the use of aphorisms, odes, humour, irony, concern for the other and the life-death relationship. The intention of the text is to demonstrate that the proposal of this book in relation to poetry is the one that the poet has always professed: poetry is the   health of language and of the soul, and an experience of humanisation.